2008
DOI: 10.1080/17453670710014851
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of PTH and bisphosphonates on the bone healing response to metaphyseal implants in rats

Abstract: Background When PTH is used to increase the amount of bone in osteoporotic patients, combination with bisphosphonates is known to attenuate the response. This might be explained by the reduced number of remodeling sites after bisphosphonate treatment, which reduces the number of cells able to respond to PTH. However, in a repair situation after trauma, a large number of osteoblasts reside in the wound site. If their activity is no longer coupled to osteoclasts, decreased resorption by bisphosphonates and stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 15 publications
3
24
1
3
Order By: Relevance
“…The finding that iPTH enhanced bone formation within our titanium implant is consistent with the beneficial effects of iPTH therapy on osseointegration seen in other models [17][18][19][20][21][22][23]35 . In our study, an increase in trabecular number, as opposed to trabecular thickness, appeared to be the primary structural change resulting from iPTH in the peri-implant region compared with the distal region.…”
Section: Peri-implantation Ipth Increased Osteoblast and Osteoclastsupporting
confidence: 76%
See 2 more Smart Citations
“…The finding that iPTH enhanced bone formation within our titanium implant is consistent with the beneficial effects of iPTH therapy on osseointegration seen in other models [17][18][19][20][21][22][23]35 . In our study, an increase in trabecular number, as opposed to trabecular thickness, appeared to be the primary structural change resulting from iPTH in the peri-implant region compared with the distal region.…”
Section: Peri-implantation Ipth Increased Osteoblast and Osteoclastsupporting
confidence: 76%
“…Previous studies of in vivo models suggested that iPTH improves osseointegration [17][18][19][20][21][22][23][29][30][31][32][33][34] . Previous studies on osseointegration, however, had substantial limitations, including (1) use of large animals (rabbits, sheep, and dogs) with accompanying high cost, lower throughput 17,19,30,31,[35][36][37][38] , and greater humanitarian concerns compared with those related to small-animal models; (2) nonphysiologic implant placement such as in the medullary canal or extra-articular locations 18,[20][21][22]32,39 ; and (3) reliance on cortical bone support for stability 18,[20][21][22]40 . In the present study, we used a newly developed murine model with an intra-articular titanium implant that was loaded through the knee joint and supported by the cancellous bone bed of the proximal part of the tibia.…”
Section: Peri-implantation Ipth Increased Osteoblast and Osteoclastmentioning
confidence: 99%
See 1 more Smart Citation
“…This direction has been pursued in the case of PTH (teriparatide). However, simultaneous treatment with PTH and bisphosphonate was not successful in improving bone mass levels (34,35). Furthermore, PTH treatment requires injection, and it has been limited to treat patients up to 2 years in western countries.…”
Section: Discussionmentioning
confidence: 99%
“…), or to change the interface between screw and bone. For example, it also appears feasible to change bone quality adjacent to Page 3 a screw post surgery, and improve pullout strength using an antiporotic drug, such as a bisphosphonate [4,34].…”
Section: Review Of Literaturementioning
confidence: 99%